Hubungan Antara Efikasi Diri Dan Dukungan Sosial Dengan Kebermaknaan Hidup Pada Penderita Tuberkulosis Paru Di Balai Pengobatan Penyakit Paru-Paru (BP4) Yogyakarta - Sedjati, Fitria (Fakultas Psikologi Universitas Ahmad Dahlan Yogyakarta, 2013)
AbstactÂ This study aimed to determine the correlation between self-efficacy and social support to the meaningfulness of life in patients with pulmonary tuberculosis who were undergoing treatment at the Medical Center Lung Disease. Subjects in this study were patients with pulmonary tuberculosis undergoing regular treatment at Medical Clinic Lung Disease Yogyakarta totaling 53 people. Measuring devices used in this research is Life Meaningfulness Scale, Self-Efficacy Scale and the Social Support Scale. Analysis of the statistical method of multiple regression analysis using SPSS 16 for windows. The results showed: (1) there was a significant relationship between self-efficacy and social support to the meaningfulness of life with R = 0.702 and p = 0.000 (p <0.01), (2) there is a significant positive relationship between self-efficacy to the meaningfulness living with r = 0606 and p = 0.000 (p <0.01), (3) there was a significant positive relationship between social support to the meaningfulness of life with r = 0.310 and p = 0.025 (p <0.05).Â Keyword: Meaningfulness of Life, Social Support, Self-Efficacy